Neurotrophic Effects of Leukemia Inhibitory Factor on Neural Cells Derived from Human Embryonic Stem Cells123. (22nd October 2012) - Majumder, Anirban; Banerjee, Saswati; Harrill, Joshua A.; Machacek, David W.; Mohamad, Osama; Bacanamwo, Methode; Mundy, William R.; Wei, Ling; Dhara, Sujoy K.; Stice, Steven L.
Abstract: Various growth factor cocktails have been used to proliferate and then differentiate human neural progenitor (NP) cells derived from embryonic stem cells (ESC) for in vitro and in vivo studies. However, the cytokine leukemia inhibitory factor (LIF) has been largely overlooked. Here, we demonstrate that LIF significantly enhanced in vitro survival and promoted differentiation of human ESC‐derived NP cells. In NP cells, as well as NP‐derived neurons, LIF reduced caspase‐mediated apoptosis and reduced both spontaneous and H2 O2 ‐induced reactive oxygen species in culture. In vitro, NP cell proliferation and the yield of differentiated neurons were significantly higher in the presence of LIF. In NP cells, LIF enhanced cMyc phosphorylation, commonly associated with self‐renewal/proliferation. Also, in differentiating NP cells LIF activated the phosphoinositide 3‐kinase and signal transducer and activator of transcription 3 pathways, associated with cell survival and reduced apoptosis. When differentiated in LIF + media, neurite outgrowth and ERK1/2 phosphorylation were potentiated together with increased expression of gp130, a component of the LIF receptor complex. NP cells, pretreated in vitro with LIF, were effective in reducing infarct volume in a model of focal ischemic stroke but LIF did not lead to significantly improved initial NP cell survival over nontreated NP cells. Our results show that LIF signaling significantly promotes human NP cell proliferation, survival, and differentiation in vitro. Activated LIF signaling should be considered in cell culture expansion systems for future human NP cell‐based therapeutic transplant studies. STEM CELLS 2012;30:2387–2399